Rapid biphasic decay of intact and defective HIV DNA reservoir during acute treated HIV disease - Alton Barbehenn; Lei Shi; Junzhe Shao; Rebecca Hoh; Heather M. Hartig; Vivian Pae; Sannidhi Sarvadhavabhatla; Sophia Donaire; Caroline Sheikhzadeh; Jeffrey Milush; Gregory M. Laird; Mignot Mathias; et al. (Nature Communications)
Abstract Despite antiretroviral therapy (ART), HIV persists in latently-infected cells (the HIV reservoir) which decay slowly over time. Here, leveraging >500 longitudinal samples from 67 people living with HIV (PLWH) treated during acute infection, we developed a mathematical model to predict reservoir decay from peripheral CD4 + T cells. Nonlinear generalized additive models demonstrated rapid biphasic decay of intact DNA (week 0-5: t1/2 ~ 2.83 weeks; week 5-24: t1/2 ~ 15.4 weeks) that extended out to 1 year. These estimates were ~5-fold faster than prior decay estimates among chronic treated PLWH. Defective DNA had a similar biphasic pattern, but data were more variable. Predicted intact and defective decay rates were faster for PLWH with earlier timing of ART initiation, higher initial CD4 + T cell count, and lower pre-ART viral load. In this study, we advanced our limited understanding of HIV reservoir decay at the time of ART initiation, informing future curative strategies targeting this critical time.